Haul Solo Tradition: Structural-Functional Analysis for the Harmonization of Multicultural Society in Surakarta - Aziz, Hafidz Al; Siregar, Riadi Syafutra; Trinugraha, Yosafat Hermawan (Universitas Tanjungpura, 2024)
This research focuses on the Haul Solo tradition, an annual cultural event that has been celebrated for hundreds of years. The tradition has become a defining characteristic of the city of Surakarta, particularly among the people of Kampung Arab. The aim of this study is to explore the congregation's interpretation of the Haul Solo tradition, the role of societal elements within it, and their function in maintaining social harmony. This study employs a qualitative approach with an ethnographic methodology. The data was collected through ethnographic interviews, participant observation, and documentation. The implementation of the Haul Solo tradition is closely tied to the roles of various societal elements, including family descendants, close relatives, santri, local government, and local society. Each element's role is adjusted according to their social status. By collaborating effectively, the multicultural structure of society is strengthened. The Haul Solo tradition serves not only as a commemoration of the death anniversary of Habib Ali Al-Habsyi, but also as a means of preserving and maintaining harmony within a multicultural society. The function of the Haul Solo tradition in bonding elements of society consists of 3 functions, religious function, social function and economic function.